2020
DOI: 10.3390/ijms21144912
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 Plays an Essential Role in Yes-Associated Protein Nuclear Translocation during the Early Phase of Trypanosoma cruzi Infection in Heart Endothelial Cells

Abstract: The protozoan parasite Trypanosoma cruzi is the causative agent of Chagas disease. This neglected tropical disease causes severe morbidity and mortality in endemic regions. About 30% of T. cruzi infected individuals will present with cardiac complications. Invasive trypomastigotes released from infected cells can be carried in the vascular endothelial system to infect neighboring and distant cells. During the process of cellular infection, the parasite induces host cells, to increase the levels of host thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…We recently showed that TSP1 plays an important role in the dysregulation of the hippo signaling pathway during the early phase of T . cruzi infection [ 55 ]. In addition, it was suggested that the Wnt/β-catenin pathway is activated early after T .…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that TSP1 plays an important role in the dysregulation of the hippo signaling pathway during the early phase of T . cruzi infection [ 55 ]. In addition, it was suggested that the Wnt/β-catenin pathway is activated early after T .…”
Section: Discussionmentioning
confidence: 99%
“…This early effect might be indicating that Tankyrases are participating in early infection-triggered mechanisms during adhesion, signalling or invasion. In heart endothelial cells, YAP (Yes-associated protein) nuclear levels are altered during the early phase of T. cruzi Infection (Arun et al ., 2020). In immortalized human Schwann cells, T. cruzi infection induces a robust activation of Akt (Chuenkova and PereiraPerrin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, YAP regulates fibrotic activity of TM cells in response to dexamethasone (Liu et al, 2021). Interestingly, TSP-1 expression is regulated by YAP/TAZ and TSP-1 can also regulate YAP/TAZ signaling (Arun et al, 2020;Yamashiro et al, 2020;Arun et al, 2022). In vascular smooth muscle cells under cyclic mechanical stretch, TSP-1 binds to integrin αvβ1 and induces focal adhesion formation to stimulate nuclear shuttling of YAP, which impacts vascular remodeling in injury models (Yamashiro et al, 2020).…”
Section: Mechanical Forces and Mechanotransduction Pathwaysmentioning
confidence: 99%
“…In vascular smooth muscle cells under cyclic mechanical stretch, TSP-1 binds to integrin αvβ1 and induces focal adhesion formation to stimulate nuclear shuttling of YAP, which impacts vascular remodeling in injury models (Yamashiro et al, 2020). In contrast, heart endothelial cells expressing TSP-1 had lower levels of unphosphorylated YAP and decreased nuclear YAP when challenged with the parasite T. cruzi as compared to endothelial cells from TSP-1 knockout mice (Arun et al, 2020). Furthermore, TSP-1 modulated YAP/β-catenin signaling in this system (Arun et al, 2022).…”
Section: Mechanical Forces and Mechanotransduction Pathwaysmentioning
confidence: 99%